Preparation, characterisation and antibacterial activity of carvacrol encapsulated in gellan gum hydrogel - Jaafar, Adila Mohamad (MDPI, 2021)
Recently, the antibacterial properties of Carvacrol (Carv) have been significantly reported. However, due to the unstable properties of Carv under various environment conditions, research approaches tailored towards its widespread and efficient use in various antimicrobial applications are scarce. Here, we discuss progress towards overcoming this challenge by utilising the encapsulation of Carv in gellan gum hydrogels to form thin films (GG-Carv) containing different concentrations of Carv (0.01–0.32 M). FTIR spectrum of GG-Carv revealed that both functional groups from GG and Carv existed. The carbon, hydrogen and nitrogen elemental analysis further supported the encapsulation of Carv with the changes in the element percentage of GG-Carv. Both swelling and degradation percentage increased with time and the decreasing patterns were observed as the concentration of Carv increased. In an antibacterial study, GG-Carv exhibited significant antibacterial activity against E. coli with the clear inhibition zone of 200 mm and the detection of bacterial growth showed enhancement with continuous decline throughout the study as compared to free-standing Carv.